Preventing type 2 diabetes: can we make the evidence work?. Issue 1007 (4th September 2009) - Yates, T; Davies, M; Khunti, K
Abstract : Type 2 diabetes is associated with many serious comorbidities and is one of the leading causes of mortality globally. Type 2 diabetes is preceded by a condition called prediabetes, which is characterised by elevated glucose concentrations resulting from peripheral and/or hepatic insulin resistance. Individuals with prediabetes have been the traditional target of diabetes prevention programmes; these have consistently shown that lifestyle modification can significantly reduce the risk of developing type 2 diabetes. This has led to the implementation of diabetes prevention initiatives in several countries. However, a number of key areas still need to be addressed. For example, important questions remain regarding how best to identify at-risk individuals and whether the findings from resource intensive research projects can be replicated using pragmatic lifestyle interventions tailored to the resources and infrastructure available to usual health care practice. This article highlights findings from diabetes prevention programmes and discusses key issues involved in translating research into practice.